Mechanical Properties of Glass Fiber Reinforced Polymers Members for Structural Applications - Landesmann,Alexandre (2015)
This paper presents the results of an experimental investigation aiming at determining the mechanical properties of Glass Fiber Reinforced Polymer (GFRP) element produced by the Brazilian industry to classify it for structural applications.. The material samples used in this work were (i) prepared in accordance to ABNT-NBR15708:2011 recommendations, (ii) extracted from web and flange parts of different geometries of one standard H-shaped GFRP single profile, (iii) 2D fiber-reinforced fibrous and (iv) exhibited fibers' orientation on the longitudinal/pultrusion direction. A fairly extensive experimental program was carried out to cover both stiffness and strength structural characteristics of GFRP element, comprising the following mechanical failures modes: (i) direct tension and compression, (ii) two-point flexural bending, (iii) pin-bearing pushed-out and (iv) interlaminar shear deformation. Based on the obtained results, it was possible to conclude that the GFRP element analyzed displays structural classification compatible to E17 class mechanical requirement.